(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Il contributo, sottoposto a valutazione, riproduce il testo nella versione integrale, completa delle note e in lingua italiana, della Comunicazione presentata al Convegno su “Islam in Europe through the Balkan Prism" (24-26 October 2013, Sarajevo). Titolo della versione inglese, destinata alla pubblicazione negli Atti, "Plural Islam in Albania: patterns of relationship with the state and religious peace". SOMMARIO: 1. Dall’Impero ottomano all’Albania indipendente 2. Le caratteristiche endogene dell’ordinamento albanese e le sue specificità - 3. Il “colonialismo giuridico” dell’Occidente e il rispetto dell’autonomia degli ordinamenti - 4. La rivisitazione delle relazioni tra Stato e Comunità religiose - 5. Estendere l’esperienza albanese agli altri Stati balcanici o quella dei Balcani all’Albania? Abstract The protection of individual and collective freedom of religion and freedom of conscience, the regulation of state relations with religious communities in Albania, have found a solution in peculiar legal rules and traditions that in the history of the Albanian people have guaranteed the religious peace. Of great significance was the Albanian legal system resistance to accept the advice of the Venice Commission, Council of Europe and the EU that would rather prefer and have sought to impose the adoption of a single political-legal model for the Balkans, focused on a general law for the protection of religious freedom. Albanian model dates back to 1923, recognizes the cultural and religious pluralism of society and the opportunity for all religious communities to obtain civil legal personality, now allows cooperation agreements with the various religious communities. The rules put as guarantees of religious freedom those of the general law without any recourse to special rules. What happened was possible because of the plural nature of Balkan Islam which has allowed mutual respect and tolerance, and thanks to the secular and separatist nature of the Albanian state since its origins. State law likewise religious rules, determined by the Statutes that communities have been given themselves and their progressive transformation have played a role in education for coexistence which has allowed, in contrast to what happened in many Balkan countries, religious peace. The smaller denominations and cults have found, and find now, legal protection, and at present are five the creeds that have concluded agreements with the state and others may do so in the future. The success of the Albanian model warns against standardization policies, substantially octroyé, supported by international bodies end one size fits all legal model/pattern.